RESILIENSI PADA PENYINTAS REVENGE PORN: RESILIENCE OF REVENGE PORN SURVIVORS - Linda Wahyuni; Nofrans Eka Saputra (Jurnal Psikologi Jambi, 2022)
ABSTRACTIntroduction The spread of non-comercial pornography, whether it’s intentionalor not, spread by known relatives or strangers, wit or without consent, and committed out of revenge can cause someone faces hardships that can put a person in a delicate and depressed condition. The delicate and depressed condition. The impacts also vary, namely psychological, physical, social, and economic impacts. These conditions require individuals to have resilience. This research aimed to discover the conception and resilience’s factors in survivor of revenge porn. Methods The method used is qualitative phenomenology. Determination of research informants was done by using purposive sampling technique. The characteristics of the informants in this research were domiciled in Jambi Province, female, aged 18-32 years, had been a victim of revenge porn, the time interval of the incident and the interview was a maximum of 1 year, and filed a report to the police. Data collection methods used are interview, observation, and documentation techniques. The data analysis used is Interpretative Phenomenological Analysis (IPA). Results The picture of resilience in revenge porn survivors includes emotion regulation, impulse control, cause analysis, empathy, self-efficacy, optimism, reaching out, and avoidance. While the influencing factors include i have, i am, i can, and spirituality. Conclusions All informants in this research showed the characteristics of resilience in revenge porn survivor with various factors. Keywords: Resilience, Revenge Porn, Revenge Porn Survivors ABSTRAKPendahuluan Penyebaran konten pornografi non-komersial dengan sengaja maupun tidak, disebarluaskan oleh orang yang dikenal maupun tidak, dilakukan tanpa persetujuan pemilik atau orang yang berada di dalam konten, serta dengan tujuan membalas dendam dapat menyebabkan seseorang berada dalam kondisi sulit dan tertekan. Dampak yang ditimbulkan pun beragam, yakni dampak secara psikologis, fisik, sosial, dan ekonomi. Kondisi tersebut mengharuskan individu memiliki resiliensi. Penelitian ini bertujuan untuk mengetahui gambaran dan faktor-faktor resiliensi pada penyintas revenge porn. Metode Metode yang digunakan adalah kualitatif fenomenologi. Peneliti menggunakan purposive sampling dengan karakteristik berdomisili di Provinsi Jambi, berjenis kelamin perempuan, berusia 18-32 tahun, penyintas revenge porn, kejadian maksimal 1 tahun lalu, serta melapor ke pihak kepolisian. Metode pengumpulan data yang digunakan adalah teknik wawancara, observasi, dan dokumentasi. Analisis data yang digunakan adalah Interpretative Phenomenological Analysis (IPA). Hasil Gambaran resiliensi penyintas revenge porn meliputi regulasi emosi, kontrol impuls, analisis penyebab, empati, efikasi diri, optimis, reaching out, dan penghindaran. Sedangkan faktor-faktor yang mempengaruhinya meliputi i have, i am, i can, dan spiritual. Kesimpulan Seluruh informan dalam penelitian ini menunjukkan karakteristik resiliensi dan faktor-faktornya. Kata kunci: Resiliensi, Penyintas Revenge Porn, Revenge Porn